Effect Of Snakehead Fish Feeding On Weight Increase In Pulmonary TB Patients In The Simpang Kanan Singkil Health Center Area In 2024 - Yusridawati, Yusridawati (Sean Institute, 2024)
Pulmonary tuberculosis is an infectious disease caused by the bacterium Tbc (Mycobacterium tuberculosis). Snakehead fish to help meet the needs of its nutrients which aim to meet the increased need for energy and protein to prevent and repair damage to body tissues. Gain weight until it reaches normal and try to balance weight with height. The purpose of this study is to determine the Effect of Snakehead Fish Feeding on Weight Gain in Pulmonary TB Patients in the SimpangKanan Singkil Health Center Area in 2024. This type of research is a Pseudo-Experiment (Quasi Experiment) with a one group pre and post test design, The population in the study of all Pulmonary TB patients is 74 people, the sampling technique uses purposive sampling and the number of samples is 25 people, The data is taken through an observation sheet and processed through an Independent T Test, The results of the study show that the body weight before being given snakehead fish is very thin in the majority of 16 respondents (64.0%) and after being thin namely 12 respondents (48%). The results of the independent statistical test T Test obtained a value of p = 0.003 > 0.05 means that there is an Effect of Snakehead Fish Feeding on Weight Gain in Pulmonary TB Patients in the SimpangKanan Singkil Health Center Area in 2024. Conclusion The study has the effect of snakehead fish on weight gain in pulmonary TB patients in the SimpangKanan Singkil Health Center area in 2024, it is expected that health workers will provide counseling on snakehead fish in increasing body weight in pulmonary TB patients